The evolution of party systems between elections - LAVER, Michael (Institutional Knowledge at Singapore Management University, 2003)
Most existing theoretical work on party competition pays little attention to the evolution of party systems between elections as a result of defections between parties. In this article, we treat individual legislators as utility-maximizing agents tempted to defect to other parties if this would increase their expected payoffs. We model the evolution of party systems between elections in these terms and discuss this analytically, exploring unanswered questions using computational methods. Under office-seeking motivational assumptions, our results strikingly highlight the role of the largest party, especially when it is “dominant” in the technical sense, as a pole of attraction in interelectoral evolution.